ヒガシ ナンキョク ソウヤ カイガン ノ リクジョウ エンガン ロガンイキ ニ テンザイスル ミコケツ サイリュウ タイシキブツ ノ リュウド ソセイ ノ トクチョウ ト セイイン - 岩崎, 正吾; イワサキ, ショウゴ; 三浦, 英樹; ミウラ, ヒデキ; 前杢, 英明; マエモク, ヒデアキ; Iwasaki, Shogo; Miura, Hideki; Maemoku, Hideaki (2005)
P(論文) 宗谷海岸露岩域に点在する未固結細粒堆積物は,従来の研究で氷成堆積物(ティル)や氷河底ティルと記載されてきたが,その成因や堆積環境について検討されたことはなかった.本研究では,未固結細粒堆積物95試料の粒度を測定し,氷河底成岩(底面氷中の岩とロッジメントティル)の粒度組成との比較によって,それらの成因を検討した.その結果,氷河底成岩は粘土から砂までの幅広いサイズの粒子で構成され,砂分と粘土分にモードが現れるバイモーダルな度分布で特徴づけられることが明らかとなった.一方,未固結細粒堆積物の大部分は主に粘土とシルトから成り,多様な粒径度分布を持つ.ただし,礫や隆起海浜堆積物に覆われる未固結細粒堆積物には氷河底成岩と同じ粒度組成を持つものがある.これらのことから,宗谷海岸露岩域の未固結細粒堆積物は,その地域にかつて広く堆積していた氷河底ティル由来の堆積物が再移動した物質を大量に含むと考えられた. Unconsolidated fine sediments (UFS), sporadically deposited in Soya Coast ice-free areas, have often been described as glacial deposits (till) or subglacial till in previous studies, but their genesis and depositional environments have never been discussed so far. In this study, 95 samples of UFS were analyzed for grain-size distribution, and their properties and origins were examined by contrast with the grain-size distribution of primary subglacial-debris (PSD): debris in basal ice and lodgement tills. Primary subglacial-debris is composed of a very broad range of grain size from clay to sand, and exhibit a typically bimodal frequency distribution with peaks in sand and clay parts. In contrast, some of the UFS covered by gravel or raised beach deposits have the same grain-size distribution with PSD, although almost all UFS consist mainly of clay and/or silt and exhibit various frequency distributions. Therefore, it seems reasonable to conclude that the UFS contains abundant reworked materials from the PSD, which were widely deposited on the Soya Coast formerly ice-free areas. departmental bulletin paper